TEACHING MASTER STUDENTS: COURSE TOPICS' COMMUNICATIVE EFFECTIVENESS - Galyna Tsapro; Olena Gryshchenko (Borys Grinchenko Kyiv Metropolitan University, 2023)
This article delves into the critical realm of teaching master students and, particularly, the communicative effectiveness embedded within the chosen course topics of «Communication Course for Master Students in Linguistics». The research is based on the questionnaire which elicits students' evaluation of topics and text genres studied. The results of the study demonstrate that certain topics resonated more profoundly with students than others. Notably, the topics of «Tying the Knot» and «Parenting» emerged as the most highly rated, indicating a heightened level of engagement among the master's students. Topics such as «When something went wrong» and «Getting through» garnered comparatively lower ratings, shedding light on potential areas for improvement or reconsideration in the curriculum. A further analysis reveals that the second year of the course received more positive feedback from students. The topic «Artificial Intelligence» stood out received the highest overall ratings among the diverse range of subjects covered in the course. This observation suggests a keen interest and appreciation for contemporary and cutting-edge themes among master's students in linguistics. Among the various text genres employed in the course, short stories emerged as the most captivating for discussions. Following closely behind were articles, poems, book chapters, and novel extracts, each contributing to the multifaceted tapestry of the students' learning experience. Students may lean towards complete short stories due to their preference for engaging, creative activities associated with literary analysis. Surprisingly, poems also garnered positive feedback, possibly because of the inventive tasks involved, like translation and responsive poem writing, fostering quick comprehension and facilitating discussions. This contrasts with more complex literary analysis, aligning with students' interest in freely conversational topics found in articles.